Correction: The Brazilian vaccine divide: How some municipalities were left behind in the Covid-19 vaccine coverage. - Antonio Fernando Boing; Alexandra Crispim Boing; Lorena Barberia; Marcelo Eduardo Borges; S V Subramanian (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0002493.].